HUBUNGAN JENIS PERSALINAN DENGAN STATUS KESEHATAN BAYI BARU LAHIR DI KOTA BUKITTINGGI - Nurhayati, Nurhayati (Maternal Child Health Care, 2019)
Every woman wants her labor to run smoothly and can give birth to a baby perfectly. Childbirth can run normally, but it is not uncommon for labor to experience obstacles and must be done through surgery. This means the fetus and mother are in an emergency and can only be saved if labor is performed by surgery. The purpose of this study is to find out the related to the health status of newborn babies at delivery in the City of Bukittinggi.Type of analytic survey research with design cross-sectional.The object of the study was a newborn baby with Caesarean section and normal delivery at Bukittinggi City Hospital. The test used is thetest Chi-Square with a 95% confidence level.The results showed that as many as 65 people (54.2%) had the incidence of asphyxia. 65 people (54.2%) had normal respiratory conditions, 62 people (51.7%) had meconium aspiration.63 people (52.5%) had trauma to an abnormal baby.64 people (53.3%) had infectious diseases. 70 people (58.3%) had IMD.72 people (60%) have joined care. 60 people (50%) with type of labor SC. Statistical tests showed that there was a relationship between apgar score (p = 0.003), respiratory conditions (p = 0.010), meconium aspiration (p = 0.0005), trauma in infants (p = 0.0005), joint care (p = 0.002 ) and IMD (p = 0.0005) for the type of labor. While infectious diseases do not have a relationship to the type of labor (p = 0.583).It was concluded that there was a relationship between apgar score, respiratory condition, meconium aspiration, admission and IMD with different types of delivery. Expected to health workers especially midwives can be used as input in order to improve health status in newborns.